Tables of inchoative verbs in the Saami languages - Kuokkala, Juha (Zenodo, 2023)
The tables in the .xlsx file present the occurrence of various types of derived inchoative verbs by tabulating the attested derivatives of each base verb in each Saami language. Base verbs are given in their Proto-Saami form and approximate meanings in Finnish. For more information about sources etc., see the paper which this is an appendix to: Kuokkala, Juha. 2023. Inchoative verbs in Saami: Derivational types and their variation. In: Saami Linguistics in Uppsala: The 2019 SAALS 4 Symposium . Studia Uralica Upsaliensia 42. Changelog: Version 1.1 - Added missing North Saami balˈlát